Random telegraph noise on the threshold voltage of multi-level flash memory - 廖轶明 纪小丽 徐跃 张城绪 郭强 闫锋 (Chinese physics B, 2017)
We investigate the impact of random telegraph noise（RTN） on the threshold voltage of multi-level NOR flash memory.It is found that the threshold voltage variation（？Vth） and the distribution due to RTN increase with the programmed level（Vth） of flash cells. The gate voltage dependence of RTN amplitude and the variability of RTN time constants suggest that the large RTN amplitude and distribution at the high program level is attributed to the charge trapping in the tunneling oxide layer induced by the high programming voltages. A three-dimensional TCAD simulation based on a percolation path model further reveals the contribution of those trapped charges to the threshold voltage variation and distribution in flash memory.